Connectivity and knowledge management in virtual organizations networking and developing interactive communications - Camison, Cesar, 1958- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
This book reviews innovations and trends in virtual organizations. Topics include knowledge creation and management, virtual customer networks, e-commerce, and virtual communities, offering analysis of the full spectrum of technologies, applications, practices, and outcomes within this field.